2010
DOI: 10.1051/0004-6361/201014156
|View full text |Cite
|
Sign up to set email alerts
|

Massive star formation in Wolf-Rayet galaxies

Abstract: Aims. We have performed a comprehensive multiwavelength analysis of a sample of 20 starburst galaxies that show a substantial population of very young massive stars, most of them classified as Wolf-Rayet (WR) galaxies. In this paper, the forth of the series, we present the global analysis of the derived photometric and chemical properties. Methods. We compare optical/NIR colours and the physical properties (reddening coefficient, equivalent widths of the emission and underlying absorption lines, ionization deg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
122
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(144 citation statements)
references
References 129 publications
22
122
0
Order By: Relevance
“…HCG 31 F is the galaxy with highest M gas /M stars ratio (and lowest M stars /L B ratio), indicating its low content of evolved stars. This result agrees with our suggestion (López-Sánchez et al 2004a) that this TDG has created stars mainly using the neutral gas from the long arm-like H i structure (Verdes-Montenegro et al 2005) found between members AC and G of the HCG 31 galaxy system. Finally, we compare some mass-to-light ratios with the colors of the galaxies.…”
Section: Analysis Of the Mass-to-light Ratiossupporting
confidence: 93%
See 4 more Smart Citations
“…HCG 31 F is the galaxy with highest M gas /M stars ratio (and lowest M stars /L B ratio), indicating its low content of evolved stars. This result agrees with our suggestion (López-Sánchez et al 2004a) that this TDG has created stars mainly using the neutral gas from the long arm-like H i structure (Verdes-Montenegro et al 2005) found between members AC and G of the HCG 31 galaxy system. Finally, we compare some mass-to-light ratios with the colors of the galaxies.…”
Section: Analysis Of the Mass-to-light Ratiossupporting
confidence: 93%
“…Indeed, HCG 31 F shows a much higher oxygen abundance than expected following the closed box model. The explanation of this behavior is that this object is a TDG that was very probably formed from the material stripped from HCG 31 AC during the fly-by encounter between member G and the A+C complex (López-Sánchez et al 2004a). The TDG has acreted a large fraction of the pre-enriched H i gas available in the arm-like structure and now hosts very intense star-formation.…”
Section: Comparison With the Closed-box Modelmentioning
confidence: 95%
See 3 more Smart Citations